Acacia Wood Bio-composites Towards Bio-Sustainability of the Environment - Rahman, Md Rezaur (Engineering Materials,, 2019)
This book investigates the enhancement of properties of acacia wood and its surface treatment for high strength bio-composites. It describes the tensile, flexural and impact strength, surface behaviour, morphological analysis, infrared spectral functional analysis, thermal properties analysis and dielectrical properties of acacia wood bio-composites. It reports efforts on the optimization of fabrication techniques to prepare acacia wood reinforced bio-composites based on PLA, PHA, Etc. The book also reports on environmental impact analysis of acacia wood bio-composites. A special chapter is dedicated to the nano-enhancement of acacia wood bio-composites and their possible use in applications in terms of sustainability and economics. .